Anatomy and Structure Secretary Hodgsonia Macrocarpa (Blume Cogn.) as Plant Traditional Medicine of the Tribe Besemah for Anti-infective and Degenerative in district Lahat, South Sumatra - Nina Tanzerina; Sarnita Sibarani; Nita Aminasih; Endri Junaidi; Juswardi (Jurnal Penelitian Pendidikan IPA, 2025)
Hodgsonia macrocarpa (Blume) Cogn. is one of the type rare cucurbita​ found in Sumatra. Plants This is a woody liana Cucurbitaceae which is abundant utilized by the tribe   Besemah in Lahat Regency, South Sumatra with Name local Still kadam, as plant drug traditional for treat disease infection including hepatitis, pneumonia, tuberculosis and other diseases degenerative namely liver. This research aims to know structure anatomy and structure secretory as well as its distribution. Study     done in the month January until April 2024, located in Sukaraja Hamlet Subdistrict Longing for Lahat Regency, South Sumatra. Research This use method descriptive and creation preparation with Paraffin and whole mount methods. Based on observation anatomy and structure secretory in H. macrocarpa namely, leaves composed of upper and lower epidermis which are covered cuticle, parenchyma palisade and sponge, network vessels, sieve cells, and non-glandular trichomes in the form of trichome single end pointed and trichome star, while trichome trichome glandular consists of from trichome conoidal and trichome headed stalk short, cell idioblast shaped round and shaped pentagon. Stem arranged by network epidermis, collenchyma, parenchyma, network vessels, found existence glandular trichomes terminal blunt, glandular trichomes terminal pointed, trichomes uniseriate, cell idioblast shaped round, crystal prisms and druse crystals. Roots arranged by epidermis, tissue cork cortex, tissue vessels, sclereids, cells idioblast shaped round, druse crystals and crystals systolic. Type structure secretory H macrocarpha in the form of glandular trichomes, cells idioblasts and crystals. While distribution structure s secretory can found in leaves, stems and roots. in H. macrocarpa. Structure secretory mentioned play a role as place storage metabolite secondary.